2016
DOI: 10.5966/sctm.2016-0085
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells as Prognostic Markers of Preterm Birth-Associated Complications

Abstract: Preterm birth is associated with alteration of the vascular tree that can result in disease states such as bronchopulmonary dysplasia and retinopathy of prematurity during the neonatal period and emphysema and hypertension in adulthood. Studies have suggested a potential role for endothelial progenitor cells in the pathophysiology of prematurity‐related complications involving blood vessels; however, this knowledge has never been synthesized. We conducted a systematic review of the published data to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Endothelial Colony Forming Cells (ECFC) are a relevant subset of endothelial progenitor cells that mainly reside in vessel wall, circulate at low frequency in the blood, and support vascular repair and de novo vessel formation 7 9 . A growing body of evidence supports their role as potential biomarkers and therapeutic targets in PT birth 5 , 10 , 11 . Among the factors that can alter cord blood ECFC functions in premature neonates, we recently demonstrated the involvement of accelerated senescence driven by sirtuin-1 (SIRT1) deficiency, which determines their vasculogenic defects 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial Colony Forming Cells (ECFC) are a relevant subset of endothelial progenitor cells that mainly reside in vessel wall, circulate at low frequency in the blood, and support vascular repair and de novo vessel formation 7 9 . A growing body of evidence supports their role as potential biomarkers and therapeutic targets in PT birth 5 , 10 , 11 . Among the factors that can alter cord blood ECFC functions in premature neonates, we recently demonstrated the involvement of accelerated senescence driven by sirtuin-1 (SIRT1) deficiency, which determines their vasculogenic defects 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, another study reported impaired cord blood ECFC self-renewal, in vivo vasculogenesis, and response to vascular endothelial growth factor from CDH infants compared with healthy term infants (46). Together with other studies using EPCs as biomarkers for neonatal complications, these observations highlight the need for larger sample sizes on clearly defined EPCs to provide more robust data (47). Overall, these findings provided sufficient rationale to test the therapeutic potential of ECFCs and MACs in animal models.…”
Section: Proof Of Concept For the Therapeutic Potential Of Epcs In Exmentioning
confidence: 77%
“…In the cord blood of preterm infants, EPC counts have been shown to be either similar to or increased versus full‐term infants, but studies of ECFC subtype proliferation and vessel formation have yielded contradictory results 54. Cord blood ECFC from preterm infants were shown to be particularly vulnerable to oxidant conditions (such as hyperoxia) with drastically impaired growth potential, disrupted nitric oxide/vascular endothelial growth factor signaling, accelerated cell senescence, as well as increased oxidative stress status 16, 17, 55.…”
Section: Discussionmentioning
confidence: 99%